2017
DOI: 10.1016/j.expneurol.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Galanin contributes to monoaminergic dysfunction and to dependent neurobehavioral comorbidities of epilepsy

Abstract: Status epilepticus (SE) in rats, along with chronic epilepsy, leads to the development of behavioral impairments resembling depressive disorder and/or attention deficit/hyperactivity disorder (ADHD), thus reflecting respective comorbidities in epilepsy patients. Suppressed neurotransmitter tone in the raphe nucleus (RN)-prefrontal cortex (PFC) serotonergic pathway and in the locus coeruleus (LC)-PFC noradrenergic pathway underlies depressive- and impulsive- like behavioral deficits respectively. We examined po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We studied the distribution of galanin, a bioactive peptide shown to modulate brainstem serotonergic and noradrenergic systems in experimental models ( Medel-Matus et al , 2017 ) and observed reduced labelling in the SUDEP groups. Galanergic neurons in the rodent medulla are concentrated in the nucleus of the solitary tract, VLM, retrotrapezoid nucleus ( Bochorishvili et al , 2012 ; Spirovski et al , 2012 ) and locus coeruleus ( Spirovski et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied the distribution of galanin, a bioactive peptide shown to modulate brainstem serotonergic and noradrenergic systems in experimental models ( Medel-Matus et al , 2017 ) and observed reduced labelling in the SUDEP groups. Galanergic neurons in the rodent medulla are concentrated in the nucleus of the solitary tract, VLM, retrotrapezoid nucleus ( Bochorishvili et al , 2012 ; Spirovski et al , 2012 ) and locus coeruleus ( Spirovski et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retrotrapezoid nucleus in animals, critical for central respiratory chemoreception, has glutamatergic and galanergic neurons that synapse with NK1R + neurons of the pre-BötC and are considered to activate breathing ( Bochorishvili et al , 2012 ); local galanin-expressing NK1R + neurons in the VLM are also activated following hypoxia and hypercapnia ( Spirovski et al , 2012 ). Other experimental studies have reported that micro-injection of galanin into the pre-BötC exerts a central respiratory depression ( Abbott et al , 2009 ) and galanin also mediates inhibition of serotonergic transmission in the medullary raphe ( Medel-Matus et al , 2017 ). Interestingly, rodent anatomical studies indicate differential sources of galanergic input to specific medullary regions; for example, there is no projection from the retrotrapezoid galanergic neurons to the medullary raphe ( Bochorishvili et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of ADHD and epilepsy may be based on several mechanisms, as underlying brain abnormalities, a genetic predisposition, a dysregulation of the neurotransmitters system [5], the chronic effects of ongoing seizures, the side effects of AEDs, and the presence of psychosocial factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from measurements of learning and memory, assessments of interictal emotional behavior in rodents have relied heavily on phenotyping batteries (23)(24)(25) to identify features of "depression-related" or "anxiety-related" behavior extrapolated from assessments of behavioral despair (e.g., forced swim test) or exploration (e.g., open field / elevated plus maze tests). While these tests are certainly convenient and offer a reasonably high throughput, they are short in duration (5-10 minutes long) and are often measured during the biological night (when lights are on).…”
Section: Introductionmentioning
confidence: 99%